2012
DOI: 10.3126/jnps.v32i2.5681
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler Study Among Children with Sickle Cell Anaemia Vs Normal Children

Abstract: Introduction: Role of transcranial Doppler in prevention of stroke in sickle cell children has been well appreciated. Studies are being done to develop the protocol in children. Since we don't find stroke very commonly in this part of the world, this study was done in order to see the prevalence of abnormal flow velocity in sickle children attending sickle cell clinic. The aims of this study were to measure mean flow velocity in different vessels in homozygous sickle cell patients using transcranial Doppler st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The results of our study are comparable with the study of Lakkhar et al 14 Lakkhar et al in their study measured velocities in middle cerebral, posterior cerebral, common carotid, internal carotid, external carotid and vertebral arteries. However, we evaluated the flow velocities in MCA only.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study are comparable with the study of Lakkhar et al 14 Lakkhar et al in their study measured velocities in middle cerebral, posterior cerebral, common carotid, internal carotid, external carotid and vertebral arteries. However, we evaluated the flow velocities in MCA only.…”
Section: Discussionsupporting
confidence: 92%
“…Following HU therapy of 2 Years, 95% (19/20) patients become transfusion independent Low dose HU therapy with no significant toxicity seems to be a useful treatment for SCA patients in Eastern India Jain et al [ 32 ] A double blind randomized controlled trial among SCA children in Central India Event rates per patient per year for VOC, blood transfusions and hospitalization in HU treated group reduced by 95.0, 94.6 and 93.1%, respectively. Also, Hb and Hb F levels were significantly higher in HU treated group than the placebo Significant haematological and clinical benefits of fixed low-dose HU (10 mg/kg/day) therapy were observed among Indian SCA patients Lakhkar et al [ 33 ] A prospective observational study involving SCA patients from Vidarbha, India 61% of children including SCA children with headache (8%) received 5–10 transfusions/year Transfusion requirement was high in this particular cohort of SCA children Jain et al [ 34 ] A retrospective analysis involving SCA children from central India Majority (62.0%) of the transfusions were required for SCA children below 5 years of age. Transfusions were mostly given when Hb level drops below 5 g/dl Clinical picture of the SCA children from central India is severe demanding frequent medical attention Jain et al [ 35 ] A prospective longitudinal study involving SCA children from Nagpur, India Rates of VOC, blood transfusions, sequestration crises, stroke, ACS and rate of hospitalizations were significantly reduced ( p < 0.001) after 2 years with HU treatment Low fixed dose HU (10 mg/kg/day) could significantly improve the haematological profile with significant clinical benefits Mehta et al [ 36 ] A descriptive study of transfusion practice for patients with SCD at a blood bank in southern Gujarat, India During the 18-week evaluation period 145 transfusion were reported for 96 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Available data suggests that transfusion was mostly given for severe anaemia (haemoglobin level below 6–7 g/dl). In addition, couple of Indian studies reported that transfusions were given when patients experience VOC [ 34 , 38 ] and headaches [ 33 ]. Nevertheless, transfusion therapy for SCD seemed to be widely used in India without clear indications which could inevitably result in many deleterious clinical outcomes in patients and increase the financial burden.…”
Section: Discussionmentioning
confidence: 99%